Current Concept in Cleft Surgery Moving Toward Excellence of Outcome and Reducing the Burden of Care - Denadai, Rafael; Lo, Lun-Jou.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book intends to cover cleft-related topics which are mainly focused on the current concept of balancing excellence in outcome and burden of cleft care. The wide spectrum of covered topics includes the understanding challenges and needs to deliver the modern surgical cleft care worldwide and comprehending multidisciplinary-based longitudinal life-changing concept. The chapters are focused on professional-friendly technical descriptions from diagnosis to execution such as nasoalveolar molding, cleft lip repair, cleft palate repair, myringotomy tube insertion, primary and secondary rhinoplasties, oronasal fistula reconstruction, velopharyngeal insufficiency management, virtual-aided alveolar reconstruction, surgery-first approach in cleft orthognathic surgery, 3D computer-assisted orthognathic surgery, revisionary surgeries, and postoperative care. Traditional and current principle-based methods are itemized into many algorithms and protocols to aid in diagnosing, planning, and selecting the best therapeutic approach in order to balance excellence in outcome and burden of care. Many surgical-, orthodontic-, speech-, and postoperative care-related technical examples, intraoperative photos, and full-colour illustrative drawings can guide the professionals working in multidisciplinary teams through each traditional and newer hybrid operative procedure in a detailed step-by-step fashion with emphasis on how to perform each procedure, rather than on theoretical-only descriptions. This book provides time- and scientifically-tested treatment algorithms to guide multidisciplinary teams during decision making process for each clinical scenario of the longitudinal cleft care.
Part I Key Concepts in Surgical Cleft Care -- 1 Epidemiological Features in Cleft Lip and Palate -- 2 The Burden of Orofacial Clefts: Global Trends and Focus on Underresourced Regions -- 3 The Unmet Need for Primary Cleft Lip and Palate Surgery: Demand for Levering Surgical Cleft Care in Underresourced Settings -- 4 Treating Cleft-Related Deformities from Initial Diagnosis to Rehabilitation into Society at Maturity: Key Concepts of Burden of Cleft Care -- 5 Longitudinal Life-Changing Concept Toward Reducing Cleft Stigmata, Dysfunction and Burden of Surgical Care -- 6 Patient-Reported Outcome Measures as Driving Factors To Transform Surgical Cleft Care -- 7 Leveraging Data Collection and Analysis To Optimize Outcomes in Surgical Cleft Care: Deciphering the Quality Improvement Puzzle -- 8 Classifying the Wide Clinical Spectrum of Cleft Lip and Palate -- Part II Surgical Cleft Care in the Growing Age -- 9 Modern Unilateral Cleft Lip and Nasal Repair: Controversies from Presurgical Orthopedics to Surgical Techniques to Postoperative Care -- 10 Current State of the Art in Unilateral Cleft Lip Repair with Primary Nasal Overcorrection: Lo$1 (Bs Modified Noordhoff$1 (Bs Procedure -- 11 Modern Bilateral Cleft Lip and Nasal Repair: Controversial Features and Guiding Principles -- 12 Current State of the Art in Bilateral Cleft Lip Repair with Primary Nasal Overcorrection: Lo$1 (Bs Modified Noordhoff$1 (Bs Procedure -- 13 Modern Cleft Palate Repair: Controversies, Surgical Techniques, and Postoperative Care -- 14 Comprehensive Appraisal of Outcome in Cleft Palate Repair -- 15 Current State of the Art in Cleft Palate Repair: Technical Description and Outcome of Lo$1 (Bs Modified Furlow$1 (Bs Double Opposing Z-Plasty Procedure -- 16 State of the Art in Surgical Management of Velopharyngeal Insufficiency -- 17 Current State of the Art in Alveolar Cleft Reconstruction: Lo$1 (Bs Modified Secondary Alveolar Bone Grafting -- Part III Surgical Cleft Care After Maturity Three-Dimensional Computer-Assisted Single-Splint Two-Jaw Cleft Orthognathic Surgery: Revisiting the Traditional Care -- 18 Three-Dimensional Computer-Assisted Single-Splint Two-Jaw Cleft Orthognathic Surgery: Revisiting the Traditional Care -- 19 Outcome of Three-Dimensional Computer-Assisted Single-Splint Two-Jaw Cleft Orthognathic Surgery -- 20 Surgical Management of Oronasal Fistula after Primary Cleft Palate Repair: Condition-Specific Protocol and Outcome -- 21 Treating Secondary Cleft Lip Deformity: Surgical Technique and Outcome -- 22 State of the Art in Secondary Cleft Rhinoplasty: Comprehensive Technical Details and Deformity-Specific Approach.s
Keywords: Surgery; Surgery; Surgery; Cleft Lip -- surgery; Cleft Palate -- surgery; Oral Surgical Procedures